Analisi Kinerja vMix Pro dalam Meningkatkan Efisiensi Produksi dan Kualitas Tayangan di RRI Banten - Agus Gilang Hermawan; Desmira Desmira (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The advancement of digital technology has had a significant impact on broadcasting production systems, including at Radio Republik Indonesia (RRI) Banten. This study aims to examine the performance of the vMix Pro application in improving production efficiency and the quality of digital broadcast programs at RRI Banten. The research employed a descriptive qualitative method, with data collected through field observations, interviews with broadcast technicians, and literature studies. The results indicate that the implementation of vMix Pro increased production time efficiency by 50%, reduced operational costs by 40%, and decreased the number of required technical operators from five to three. In terms of quality, both video and audio outputs showed improvement, achieving an average score above 4.6 on a 5-point scale, reflecting more stable, clear, and professional broadcasts. With its user-friendly interface and high device integration capability, vMix Pro has proven effective in streamlining workflows, optimizing resource utilization, and enhancing the overall production quality of broadcasts at RRI Banten